Analisis Pengaruh Kecerdasan Spiritual terhadap Motivasi Belajar Siswa Sekolah Dasar Menggunakan Pendekatan Korelasional - Darman Setia Zebua (P3M STT Kristus Alfa Omega, 2026)
The problem in this study is to determine whether there is an influence of spiritual intelligence on children’s learning motivation, considering that in the field conditions students have low learning motivation even though the school has attempted to develop students’ spiritual intelligence through spiritual and religious activities. This study aims to measure and analyze the influence of spiritual intelligence on learning motivation. This research uses a quantitative-correlational research method. The total population in this study consisted of 32 students. The data collection technique used was a questionnaire. Furthermore, the data in this study were analyzed using the Pearson Product Moment correlation technique to determine the positive correlation and the coefficient of determination to identify the contribution of spiritual intelligence to learning motivation. The results of the study indicate that there is a positive influence between spiritual intelligence and learning motivation among students of SD Negeri Jatisari Semarang, with a contribution of 55.3% to learning motivation. These findings prove that students with spiritual intelligence are able to explore and discover meaning and purpose in every activity they undertake, which in turn can increase each student’s motivation to learn.